Multidrug-Resistant Organisms and Their Association with Risk Factors; A Study at the Intensive Care Unit of Tertiary Care Hospital, Peshawar - Sarwar, Mariam; Fuad Ahmad Siddiqi; Salman Riaz; Ammad Hasan Chaudhry; Muhammad Hassan; Ashfaq Hussain (Pakistan Armed Forces Medical Journal, 2023)
Objective: To investigate rates of multidrug-resistant organisms (MDRO) infection, their antimicrobial resistance (AMR) patterns, and risk factors for acquisition of such infections at a Tertiary-Care Hospital ICU.Study Design: Cross sectional study.Place and Duration of Study: Adult Intensive Care Unit of Tertiary Care Hospital, Peshawar Pakistan, from Jan to Dec 2022.Methodology: All patients admitted to adult ICU who developed signs/symptoms of infection after 48 hours of admission were investigated. Microbiological diagnosis was done via standard microbiological practices, and if the patient had acquired an MDRO infection, it was included in the study.Results: During the study, 92 patients acquired MDRO infection in total. The most common source was blood (43.5%). The most common organisms isolated were Klebsiella pneumoniae (21.7%), Acinetobacter baumannii (20.7%) and Pseudomonasaeruginosa (17.4%). The highest percentage of resistance among Gram-positive organisms was exhibited to Penicillin and Co-amoxiclav (91%). Gram-negative isolates exhibited high overall resistance to all used antibiotic classes. The least frequency of resistance was recorded for Tigecycline (1%) against Klebsiella pneumoniae and 33% against Escherichia coli, while 32% Acinetobacter baumannii and 25% Pseudomonas aeruginosa were Colistin/Polymyxin resistant; none of the Klebsiella pneumoniae showed Colistin resistance.Conclusion: Antimicrobial resistance in our setup was high among Gram-negative and Gram-positive organisms. The most common risk factor was central line placement among the patients, highlighting the importance of infection control measures and the need to implement infection control bundles to circumvent infections due to invasive devices.